A novel hybrid dew point cooling system for mobile applications - Worall, Mark; Dicken, Adam; Shatat, Mahmood; Gledhill, Sam; Riffat, Saffa (2018)
A novel dew point cooling system for truck cabin cooling has been designed and tested, which shows excellent performance in environments of low to medium relative humidity. Experimental results showed that cooling capacity of over 1kW could be achieved with up to 12K of sensible cooling of the supply air and a COP of up to 7. The DPC unit can provide comfort cooling to a vehicle using a rooftop unit whose DPC core is no larger than 0.5m x 0.5m x 0.25m.